WaVeSim - waterv vehicle simulator - António Nogueira Santos (2006)
This article introduces a new framework for the simulation of multiple water vehicles operating simultaneously. Its main goal is to be used as a testing tool to help the development and implementation of the vehicles on-board software. This simulator provides real-time realistic dynamic behaviour of underwater and surface vehicles as well as acoustic navigation by simulating acoustic signal propagation and providing acoustic transducers on vehicles and pre-located buoys. Pressure, temperature, condutivity, salinity and sonar sensors emulation is also provided and water flows can also be defined. There should be no intrusion in the existing software and a small SDK is available to help building a broker application that makes the bridge between the software and the simulator, both possibly running on different network peers. A provided 3D visualization system may also be used to control and watch the simulation.